Primary conjunctival tuberculosis: A rare masquerading entity (Indian Journal of Case Reports, 2019)
Primary conjunctival tuberculosis is a rare entity in India. Here, we report a rare case of bilateral primary conjunctival tuberculosis in a 20-years-old female. She had multiple granular lesions in both the eyes for one year and was not responding to topical antibiotic or steroids. Slit-lamp examination showed multiple small subconjunctival granulomas. Conjunctival excision-biopsy revealed granulomatous inflammation with caseous necrosis. A diagnosis of primary conjunctival tuberculosis was made and anti-tubercular therapy was started to which the patient responded rapidly with complete resolution of the lesions by 2 months. Histopathological examination of chronic non-resolving inflammatory conjunctival lesions is important as it may be a rare presentation of a disease like tuberculosis.